2016
DOI: 10.1364/ol.41.005003
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot diffraction-limited imaging through scattering layers via bispectrum analysis

Abstract: Recently introduced speckle-correlations based techniques enable noninvasive imaging of objects hidden behind scattering layers. In these techniques the hidden object Fourier amplitude is retrieved from the scattered light autocorrelation, and the lost Fourier phase is recovered via iterative phase-retrieval algorithms, which suffer from convergence to wrong local-minima solutions and cannot solve ambiguities in object-orientation. Here, inspired by notions used in astronomy, we experimentally demonstrate that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 24 publications
(38 reference statements)
2
40
0
Order By: Relevance
“…The solution is to use instead process the recorded speckle data using bispectrum processing (e.g. [8]) which recovers the absolute phase of the object up to an overall phase gradient. The recovered object from bispectrum processing can then be used as an initial-guess in further runs of an iterative phase retrieval algorithm to further refine the result.…”
Section: A the Twin-image Problemmentioning
confidence: 99%
“…The solution is to use instead process the recorded speckle data using bispectrum processing (e.g. [8]) which recovers the absolute phase of the object up to an overall phase gradient. The recovered object from bispectrum processing can then be used as an initial-guess in further runs of an iterative phase retrieval algorithm to further refine the result.…”
Section: A the Twin-image Problemmentioning
confidence: 99%
“…Indeed, it has been demonstrated that a speckle pattern propagated through clear space contains enough information to reconstruct the image of an object [5]. Recently, a variety of approaches have been demonstrated to solve this problem, such as time-of-flight imaging [6], time reversal or phase conjugation [7][8][9][10][11][12][13][14], transmission matrix measurement [15][16][17][18], wavefront shaping technique [19][20][21][22][23], digital holography [24][25][26][27], speckle auto-correlation method [28][29][30][31][32][33][34], and other speckle correlation methods [35,36]. The transmission matrix fully characterizes the effect of a scattering medium.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the accuracy of the resulting ME video and potentially make it more robust to imperfect recovery of the associated speckle subframes, alternative approaches to the image recovery may be used. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%